Variability of the Chemical Composition of Cork - Pereira, Helena (BioResources, 2013)
The chemical composition of cork was determined, following a sampling that covered the whole production area in Portugal (29 provenances from six regions) with samples taken at cork stripping. To analyse between population variations, a more intensive sampling was made in two locations. The overall mean chemical composition of cork was: extractives 16.2% (dichloromethane 5.8%, ethanol 5.9%, water 4.5%), suberin 42.8% (long-chain lipids 41.0%, glycerol 3.8%), and lignin 22.0% (Klason 21.1%, acid soluble 0.9%). The suberin compositional ratio of long chain lipids to glycerol, LCLip:Gly, was 11.3. The proportion of neutral sugars in the polysaccharides was: glucose 46.1%, xylose 25.1%, arabinose 18.0%, mannose 3.0%, galactose 7.3%, and rhamnose 0.5%. The range of values was large and the variation between individual trees seemed to be the major factor of the differences. Geographical location of cork production was statistically significant only in a few cases when considering site and not when considering regions. The population variation in two sites was important and the absolute difference between the site mean values was small. This research covers the natural variability of cork’s chemical composition and discusses the contribution of the structural compounds to the variation of cork properties.
Keywords: chemical composition; Cork; Extractives; Lignin; Quercus suber; suberin

An integrated approach to understanding the sorption mechanism of phenanthrene by cork. - Olivella, M. À; Jové, P.; Bianchi, A.; Bazzicalupi, C.; Cano, L. (Chemosphere, 2012)
Previous studies have shown the high sorption affinity of polycyclic aromatic hydrocarbons by cork. The aim of the present work is to go further by investigating the sorption mechanism of polycyclic aromatic hydrocarbons (exemplified by phenanthrene) on cork and the availability of the chemical components (i.e. lignin, suberin, holocellulose and extractives) to retain phenanthrene. Two approaches were integrated to reach this objective: (1) statistical multivariate analysis to obtain correlations between the sorption capacity, measured as K(oc), and the sorbent properties (i.e. polarity, acidic functional groups, %dichloromethane extractives, %ethanol and water extractives, %suberin, %lignin and %holocellulose) and (2) modeling calculations to obtain information on interaction at the molecular level. The statistical multivariate analysis demonstrated a strong and positive correlation between K(oc) and the lignin content as well as negative correlations between K(oc) and the phenolic groups and %dichloromethane extractives contents. The modeling study showed that the lignin-phenanthrene interaction is mostly hydrophobic in nature being largely determined by the π-stacking interaction between the aromatic groups of the interacting partners. This result justifies the observed correlations as dichloromethane extractives, being hydrophobic, compete with phenanthrene adsorption, whereas phenolic groups, as well as negatively charged groups, enhance the hydrophilic character of the sorbent surface, thus hindering the adsorption of phenanthrene.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 23149185
Keywords: Biopolymer; Biosorption; Lignin; PAHs; p–p Interactions; suberin

Tree Species Effect on Litter Decomposition and Nutrient Release in Mediterranean Oak Forests Changes Over Time - Aponte, Cristina; García, Luis V.; Marañón, Teodoro (Ecosystems, 2012)
ree species can affect the decomposition process through the quality of their leaf fall and through the species-speciﬁc conditions that they generate in their environment. We compared the relative importance of these effects in a 2-year experiment. Litterbags containing leaf litter of the winter-deciduous Quercus canariensis, the evergreen Q. suber and mixed litter were incubated beneath distinct plant covers. We measured litter carbon loss, 9 macro- and micronutrients and 18 soil chemical, physical and biological parameters of the incubation environment. Tree species affected decay dynamics through their litter quality and, to a lesser extent, through the induced environmental conditions. The deciduous litter showed a faster initial decomposition but left a larger fraction of slow decomposable biomass compared with the perennial litter; in contrast the deciduous environment impeded early decomposition while promoting further carbon loss in the latter decay stages. The interaction of these effects led to a negative litter–environment interaction contradicting the home-ﬁeld advantage hypothesis. Leaf litter N, Ca and Mn as well as soil N, P and soil moisture were the best predictors for decomposition rates. Litter N and Ca exerted counteractive effects in early versus late decay stages; Mn was the best predictor for the decomposition limit value, that is, the fraction of slowly decomposable biomass at the later stage of decomposition; P and soil moisture showed a constant and positive relation with carbon loss. The deciduous oak litter had a higher initial nutrient content and released its nutrients faster and in a higher proportion than the perennial oak litter, signiﬁcantly increasing soil fertility beneath its canopy. Our ﬁndings provide further insights into the factors that control the early and late stages of the decomposition process and reveal potential mechanisms underlying tree species inﬂuence on litter decay rate, carbon accumulation and nutrient cycling.
Keywords: decomposition limit value; Lignin; litter chemistry; litterbag; Plant–soil interactions; Quercus; Soil fertility

Nutrient dynamics in litter mixtures of four Mediterranean maquis species decomposing in situ - Maisto, Giulia; De Marco, Anna; Meola, Angela; Sessa, Ludovica; Virzo De Santo, Amalia (Soil Biology and Biochemistry, 2011)
In natural conditions, litters shed from different species become mixed with each other, and decompose together. Most studies deal with decomposition of individual species; few studies investigate the inﬂuence of litter mixing on decomposition and nutrient dynamics; the results are contradictory as positive, negative, or no effect, of litter mixing have been observed. In this study we test the hypothesis: i) that litter mixing in the Mediterranean maquis, a nutrient poor, high diversity ecosystem, produces non-additive effects on nutrient dynamics; ii) that the effects vary with the composition in species of the mixture and with the relative amount of the species component the mixture. Two types of 3-species mixtures were set up; one contained three sclerophylls, Phillyrea angustifolia, Pistacia lentiscus and Quercus ilex; the other contained the ﬁrst two species with the mesophyll Cistus. Litterbags, containing monospeciﬁc litters and even and uneven mixtures, were incubated under natural condition in situ; even mixtures had the 3 species in equal proportion, whereas uneven mixtures had one of the species as dominant (50%) and the other two species in equal proportion (25%:25%). Litterbags were retrieved after 92, 188 and 403 days; litters from the mixtures were separately analyzed for mass loss and content of nitrogen (N), potassium (K), sodium (Na), calcium (Ca), magnesium (Mg), manganese (Mn), iron (Fe), copper (Cu), and zinc (Zn). Results indicate that mixing inﬂuences the dynamics of N, Mn, Ca, Mg, Fe, Cu and Zn, but scarcely affects the dynamics of K and Na. The comparison of observed to expected values for changes of nutrients in litterbags indicates the occurrence of non-additive effects of litter mixing on movements of N, Fe, Cu, and Zn to or from the litterbags containing the mixtures. The effects depend on the composition in species of the mixture, whereas the relative amount of the species component the mixture is not relevant.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Interactions among litters; Lignin; litter decomposition; Manganese; Non-additive effects of litter mixing

Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism

The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna (Journal of Environmental Science and Health, Part A, 2011)
The aim of this study is to determine the sorption-desorption behavior of a mixture of thirteen aqueous PAHs on cork waste at a particle of size 0.25?0.42 mm obtained from the remains of cork strips. The final purpose is to use this natural adsorbent as an alternative to activated carbon in an innovative approach for the removal of this class of toxic compounds, and significantly reduce the regeneration costs of the process. The chemical composition of the selected cork revealed that suberin (38.5 %) and lignin (31.6 %) were the main structural components of the cell wall. The high efficiency of cork as a biosorbent of PAHs is shown by the fact that just over 80 % of adsorption occurred during the first two minutes of contact time. Both Freundlich's and Langmuir's isotherms gave good fits to the sorption process. The highest adsorption affinities were exhibited for pyrene, anthracene, and phenanthrene. Desorption studies indicate a high degree of irreversibility for all PAHs, and especially so in the case of high molecular PAHs. The correlation with KF and low molecular weight PAHs was the most significant. The quantity of cork required to reduce water pollution was estimated to be between 3 and 15 times less than the quantities required in the case of other materials (i.e. aspen wood and leonardite). This study demonstrates for the first time that cork is a potential biosorbent for PAHs and may have relevance in the future treatment of PAH-contaminated waters.
From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)The following values have no corresponding Zotero field: publisher: Taylor & Francis accession-num: 21644164
Keywords: Adsorption; Aromatic; Aromatic: chemistry; biosorbent; Chemical; Chemical: chemistry; Cork waste; Environmental Remediation; Environmental Remediation: methods; Gas Chromatography-Mass Spectrometry; Lignin; Lignin: chemistry; Lipids; Lipids: chemistry; organic pollutants; PAHs; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Solid Phase Microextraction; sorption-desorption; Time Factors; Water Pollutants; water treatment

EFECTO DE FERTILIZANTES SOBRE LA PRODUCCIÓN DE BIOMASA Y PARÁMETROS DE CALIDAD EN PASTOS HERBÁCEOS DE DEHESA DESPUÉS DE TRES AÑOS CONTINUADOS DE APLICACIÓN - SANTAMARÍA, O.; Poblaciones, M. J.; Olea, L.; Rodrigo, S.; VIGUERA, F. J.; GARCÍA-WHITE, T. (PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes, 2010)
Dehesa is an agrosilvopastoral system widespread in southwestern Iberian Peninsula. Natural pastures, which are the main source, could be improved by using a proper fertilization, among other practices. With the aim of evaluating the effect of different fertilizers on biomass production and sev- eral nutritive value parameters (crude protein, fiber and lignin) of the pasture in comparison with the traditionally used superphosphate, a study was initiated in 2006/07. In the present communication, the third-year-results (2008/09) are presented. The study was carried out in a dehesa located in Extre- madura, in two areas: one with natural pastures and other with sown pastures. Eight surface-broadcast fertilization treatments were done in autumn. Two grazing periods were simulated by cutting the pas- ture in middle-spring and late-spring. Although no statistical differences were found among treat- ments, fertilizers tended to increase biomass production in comparison to the non-fertilized control; in some cases (treatment M1in the sown pasture) increments were close to 50%. Regarding the nutritive value, treatment T2 (the highest doses of Thomaskali fertilizer, 300 kg·ha-1) produced biomass with the significant highest protein content
The following values have no corresponding Zotero field: periodical: PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes pub-location: Zamora
Keywords: crude protein; fiber; Lignin; natural pasture; sown pasture

Microbial activity and quality changes during decomposition of Quercus ilex leaf litter in three Mediterranean woods - Papa, S.; Pellegrino, A.; Fioretto, A. (Applied Soil Ecology, 2008)
Changes in enzyme activities during litter decomposition provide diagnostic information on the dynamics of decay and functional microbial succession. Here we report a comparative study of enzyme activities involved in the breakdown of major plant components and of other key parameters (microbial respiration, fungal biomass, N, lignin and cellulose contents) in homogeneous leaf litter of Quercus ilex L. incubated in three evergreen oak woods in Southern Italy (Campania), differing for chemical and physical soil characteristics and microclimatic conditions. The results showed that the litter mass loss rates were similar in the three wood sites. Independently of the incubation sites, cellulase, xylanase and peroxydase activities showed seasonal variations with maximum and minimum levels in wet and dry periods, respectively, and this pattern closely matched microbial respiration. Activities of a- and b-amylase, instead, were high at the beginning of incubation and quickly decreased with decomposition progress because their substrate was rapidly depleted. Laccase activity, in contrast, was low at the beginning of incubation but after 6 months it increased signiﬁcantly. The increase of laccase activity was correlated to an increase in fungal biomass, probably reﬂecting a major shift in the litter microbial community. As concerns quality changes, N and lignin content did not signiﬁcantly change during decay. The cellulosic component started being degraded after about 6 months in the litter incubated in two of the three wood sites and from the start of decomposition in the third site. Apart from minor differences in the levels of certain enzyme activities, the data showed that the functional microbial succession involved in the decomposition of Q. ilex leaf litter did not change appreciably in response to differences in soil and microclimatic conditions in the incubation sites.
Keywords: Cellulose; Enzyme activities; Fungal biomass; Lignin; litter decomposition; Microbial respiration

Microbial activity and quality changes during decomposition of Quercus ilex leaf litter in three Mediterranean woods - Papa, S; Pellegrino, a; Fioretto, a (Applied Soil Ecology, 2008)
Changes in enzyme activities during litter decomposition provide diagnostic information on the dynamics of decay and functional microbial succession. Here we report a comparative study of enzyme activities involved in the breakdown of major plant components and of other key parameters (microbial respiration, fungal biomass, N, lignin and cellulose contents) in homogeneous leaf litter of Quercus ilex L. incubated in three evergreen oak woods in Southern Italy (Campania), differing for chemical and physical soil characteristics and microclimatic conditions. The results showed that the litter mass loss rates were similar in the three wood sites. Independently of the incubation sites, cellulase, xylanase and peroxydase activities showed seasonal variations with maximum and minimum levels in wet and dry periods, respectively, and this pattern closely matched microbial respiration. Activities of a- and b-amylase, instead, were high at the beginning of incubation and quickly decreased with decomposition progress because their substrate was rapidly depleted. Laccase activity, in contrast, was low at the beginning of incubation but after 6 months it increased signiﬁcantly. The increase of laccase activity was correlated to an increase in fungal biomass, probably reﬂecting a major shift in the litter microbial community. As concerns quality changes, N and lignin content did not signiﬁcantly change during decay. The cellulosic component started being degraded after about 6 months in the litter incubated in two of the three wood sites and from the start of decomposition in the third site. Apart from minor differences in the levels of certain enzyme activities, the data showed that the functional microbial succession involved in the decomposition of Q. ilex leaf litter did not change appreciably in response to differences in soil and microclimatic conditions in the incubation sites.
Keywords: Cellulose; Enzyme activities; Fungal biomass; Lignin; litter decomposition; Microbial respiration

Decomposition dynamics of Myrtus communis and Quercus ilex leaf litter: Mass loss, microbial activity and quality change - Fioretto, A.; Papa, S.; Pellegrino, A.; Fuggi, A. (Applied Soil Ecology, 2007)
The patterns of microbial respiration and enzyme activity (cellulase, xylanase, laccase and peroxidase) in the leaf litter of two evergreen sclerophyll species, Myrtus communis and Quercus ilex, were compared during decay in a low shrubland and in a coppice wood in a Natural Reserve in the Mediterranean area. The two litter types had similar initial amounts of lignin, cellulose and acid-detergentsoluble substances, but the litter from M. communis had a lower N content and higher C/N ratio. In spite of this, the decomposition rate of M. communis litter was higher than for Q. ilex. Whilst no seasonal variation was observed in the rate of organic matter degradation, respiration and extractable cellulase and xylanase activities showed seasonal variation in both litter types with the highest values in winter–early spring and the lowest in summer, and showed positive correlations with water content. Peroxidase activity exhibited a seasonal pattern and was higher in Q. ilex than in M. communis, while laccase activity was higher in M. communis and increased with fungal biomass as degradation progressed. Nevertheless, no relationship was found between laccase and peroxidase activity and lignin degradation. The results obtained indicate that the seasonal alternation of moist and dry periods is the major factor inﬂuencing soil biological activity in the Mediterranean area. The occurrence of pronounced seasonal variation in litter enzyme activity prevents the determination of possible correlations with litter mass loss.
Keywords: Cellulose; Enzyme activity; Fungal biomass; Lignin; litter decomposition; Microbial respiration

Decomposition dynamics of Myrtus communis and Quercus ilex leaf litter: Mass loss, microbial activity and quality change - Fioretto, a; Papa, S; Pellegrino, a; Fuggi, A (Applied Soil Ecology, 2007)
The patterns of microbial respiration and enzyme activity (cellulase, xylanase, laccase and peroxidase) in the leaf litter of two evergreen sclerophyll species, Myrtus communis and Quercus ilex, were compared during decay in a low shrubland and in a coppice wood in a Natural Reserve in the Mediterranean area. The two litter types had similar initial amounts of lignin, cellulose and acid-detergentsoluble substances, but the litter from M. communis had a lower N content and higher C/N ratio. In spite of this, the decomposition rate of M. communis litter was higher than for Q. ilex. Whilst no seasonal variation was observed in the rate of organic matter degradation, respiration and extractable cellulase and xylanase activities showed seasonal variation in both litter types with the highest values in winter–early spring and the lowest in summer, and showed positive correlations with water content. Peroxidase activity exhibited a seasonal pattern and was higher in Q. ilex than in M. communis, while laccase activity was higher in M. communis and increased with fungal biomass as degradation progressed. Nevertheless, no relationship was found between laccase and peroxidase activity and lignin degradation. The results obtained indicate that the seasonal alternation of moist and dry periods is the major factor inﬂuencing soil biological activity in the Mediterranean area. The occurrence of pronounced seasonal variation in litter enzyme activity prevents the determination of possible correlations with litter mass loss.
Keywords: Cellulose; Enzyme activity; Fungal biomass; Lignin; litter decomposition; Microbial respiration

Lignin and cellulose degradation and nitrogen dynamics during decomposition of three leaf litter species in a Mediterranean ecosystem - Fioretto, Antonietta; Di Nardo, Carmelina; Papa, Stefania; Fuggi, Amodio (Soil Biology and Biochemistry, 2005)
Cellulose and lignin degradation dynamics was monitored during the leaf litter decomposition of three typical species of the Mediterranean area, Cistus incanus L., Myrtus communis L. and Quercus ilex L., using the litter bag method. Total N and its distribution among lignin, cellulose and acid–detergent–soluble fractions were measured and related to the overall decay process. The litter organic substance of Cistus and Myrtus decomposed more rapidly than that of Quercus. The decay constants were 0.47 yearK1 , 0.75 yearK1 and 0.30 yearK1 for Cistus, Myrtus and Quercus, respectively. Lignin and cellulose contents were different as were their relative amounts (34 and 18%, 15 and 37%, 37 and 39% of the overall litter organic matter before exposure, for Cistus, Myrtus and Quercus, respectively). Lignin began to decrease after 6 and 8 months of exposure in Cistus and Myrtus, respectively, while it did not change signiﬁcantly during the entire study period in Quercus. The holocellulose, in contrast, began to decompose in Cistus after 1 year, while in Quercus and Myrtus immediately. Nitrogen was strongly immobilized in all the litters in the early period of decay. Its release began after the ﬁrst year in Cistus and Myrtus and after 2 years of decomposition in Quercus. These litters still contained about 60, 20 and 90% of the initial nitrogen at the end of the experiment (3 years). Prior to litter exposure nitrogen associated with the lignin fraction was 65, 54 and 37% in Cistus, Myrtus and Quercus, while that associated with the cellulose fraction was 30, 24 and 28%. Although most of the nitrogen was not lost from litters, its distribution among the litter components changed signiﬁcantly during decomposition. In Cistus and Myrtus the nitrogen associated with lignin began to decrease just 4 months after exposure. In Quercus this process was slowed and after 3 years of decomposition 8% of the nitrogen remained associated with lignin or lignin-like substances. The nitrogen associated with cellulose or cellulose-like substances, in contrast, began to decrease from the beginning of cellulose decomposition in all three species. At the end of the study period most of the nitrogen was not associated to the lignocellulose fraction but to the acid–detergent–soluble substance (87, 88 and 84% of the remaining litter nitrogen).
Keywords: Cellulose; cistus incanus; decomposition dynamics; Lignin; myrtus communis; nitrogen; Quercus ilex

Lignin and cellulose degradation and nitrogen dynamics during decomposition of three leaf litter species in a Mediterranean ecosystem - Fioretto, Antonietta; Di Nardo, Carmelina; Papa, Stefania; Fuggi, Amodio (Soil Biology and Biochemistry, 2005)
Cellulose and lignin degradation dynamics was monitored during the leaf litter decomposition of three typical species of the Mediterranean area, Cistus incanus L., Myrtus communis L. and Quercus ilex L., using the litter bag method. Total N and its distribution among lignin, cellulose and acid–detergent–soluble fractions were measured and related to the overall decay process. The litter organic substance of Cistus and Myrtus decomposed more rapidly than that of Quercus. The decay constants were 0.47 yearK1 , 0.75 yearK1 and 0.30 yearK1 for Cistus, Myrtus and Quercus, respectively. Lignin and cellulose contents were different as were their relative amounts (34 and 18%, 15 and 37%, 37 and 39% of the overall litter organic matter before exposure, for Cistus, Myrtus and Quercus, respectively). Lignin began to decrease after 6 and 8 months of exposure in Cistus and Myrtus, respectively, while it did not change signiﬁcantly during the entire study period in Quercus. The holocellulose, in contrast, began to decompose in Cistus after 1 year, while in Quercus and Myrtus immediately. Nitrogen was strongly immobilized in all the litters in the early period of decay. Its release began after the ﬁrst year in Cistus and Myrtus and after 2 years of decomposition in Quercus. These litters still contained about 60, 20 and 90% of the initial nitrogen at the end of the experiment (3 years). Prior to litter exposure nitrogen associated with the lignin fraction was 65, 54 and 37% in Cistus, Myrtus and Quercus, while that associated with the cellulose fraction was 30, 24 and 28%. Although most of the nitrogen was not lost from litters, its distribution among the litter components changed signiﬁcantly during decomposition. In Cistus and Myrtus the nitrogen associated with lignin began to decrease just 4 months after exposure. In Quercus this process was slowed and after 3 years of decomposition 8% of the nitrogen remained associated with lignin or lignin-like substances. The nitrogen associated with cellulose or cellulose-like substances, in contrast, began to decrease from the beginning of cellulose decomposition in all three species. At the end of the study period most of the nitrogen was not associated to the lignocellulose fraction but to the acid–detergent–soluble substance (87, 88 and 84% of the remaining litter nitrogen).
Keywords: Cellulose; cistus incanus; decomposition dynamics; Lignin; myrtus communis; nitrogen; Quercus ilex

Photosynthesis, Soluble and Structural Carbon Compounds in Two Mediterranean Oak Species (Quercus pubescens and Q. ilex) after Lifetime Growth at Naturally Elevated CO2 Concentrations - Blaschke, L.; Schulte, M.; Raschi, A.; Slee, N.; Rennenberg, H.; Polle, A. (Plant Biology, 2001)
Abstract: To study physiological responses of mature forest trees to elevated CO2 after lifetime growth under elevated atmospheric CO2 concentrations (pCO2), photosynthesis, Rubisco content, foliar concentrations of soluble sugars and starch, sugar concentrations in transport tissues (phloem and xylem), structural biomass, and lignin in leaves and branches were investigated in 30- to 50-year-old Quercus pubescens and Q. ilex trees grown at two naturally elevated CO2 springs in Italy. Ribulose-1,5-bisphosphate carboxylase/oxygenase content was decreased in Q. pubescens grown under elevated CO2 concentrations, but not in Q. ilex. Photosynthesis was consistently higher in Q. pubescens grown at elevated CO2 as compared with “control” sites, whereas the response in Q. ilex was less pronounced. Stomatal conductance was lower in both species leading to decreased transpiration and increased instantaneous water use efficiency in Q. pubescens. Overall mean sugar + starch concentrations of the leaves were not affected by elevated pCO2, but phloem exudates contained higher concentrations of soluble sugars. This finding suggests increased transport to sinks. Qualitative changes in major carbon-bearing compounds, such as structural biomass and lignins, were only found in bark but not in other tissues. These results support the concept that the maintenance of increased rates of photosynthesis after long-term acclimation to elevated pCO2 provides a means of optimization of water relations under arid climatic conditions but does not cause an increase in aboveground carbon sequestration per unit of tissue in Mediterranean oak species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Carbohydrate; climate change; Elevated CO2; Lignin; photosynthesis; Rubisco

Photosynthesis, Soluble and Structural Carbon Compounds in Two Mediterranean Oak Species (Quercus pubescens and Q. ilex) after Lifetime Growth at Naturally Elevated CO2 Concentrations - Blaschke, L; Schulte, M; Raschi, A; Slee, N; Rennenberg, H; Polle, A (Plant Biology, 2001)
Abstract: To study physiological responses of mature forest trees to elevated CO2 after lifetime growth under elevated atmospheric CO2 concentrations (pCO2), photosynthesis, Rubisco content, foliar concentrations of soluble sugars and starch, sugar concentrations in transport tissues (phloem and xylem), structural biomass, and lignin in leaves and branches were investigated in 30- to 50-year-old Quercus pubescens and Q. ilex trees grown at two naturally elevated CO2 springs in Italy. Ribulose-1,5-bisphosphate carboxylase/oxygenase content was decreased in Q. pubescens grown under elevated CO2 concentrations, but not in Q. ilex. Photosynthesis was consistently higher in Q. pubescens grown at elevated CO2 as compared with “control” sites, whereas the response in Q. ilex was less pronounced. Stomatal conductance was lower in both species leading to decreased transpiration and increased instantaneous water use efficiency in Q. pubescens. Overall mean sugar + starch concentrations of the leaves were not affected by elevated pCO2, but phloem exudates contained higher concentrations of soluble sugars. This finding suggests increased transport to sinks. Qualitative changes in major carbon-bearing compounds, such as structural biomass and lignins, were only found in bark but not in other tissues. These results support the concept that the maintenance of increased rates of photosynthesis after long-term acclimation to elevated pCO2 provides a means of optimization of water relations under arid climatic conditions but does not cause an increase in aboveground carbon sequestration per unit of tissue in Mediterranean oak species.
Keywords: Carbohydrate; climate change; Elevated CO2; Lignin; photosynthesis; Rubisco

Comparative Analysis of the Lignins of Cork from Quercus suber L. and Wood from Eucalyptus globulus L. by Dry Hydrogen Iodide Cleavage - Akim, L G; Cordeiro, N; Pascoal Neto, C; Gandini, A (Lignin: Historical, Biological, and Materials Perspectives, 1999)
Lignin from cork (Quercus suber L.) was isolated by two procedures: organosolv extraction and dioxane-water (9:1) extraction in presence of HCl. These lignins were characterized using a mild hydrogen iodide-cleavage method followed by 1H NMR and GPC analysis. The results were compared with those for eucalyptus lignins (Eucalyptus globulus) isolated by the same procedures. The method used provided syringyl/guaiacyl ratios for the linear parts of the macromolecules and the degrees of crosslinking. The prevalence of guaiacyl units was demonstrated for cork lignin. Syringyl units were found to be minor components and present mainly in the linear parts of macromolecules. p-Hydroxyphenyl units were mainly condensed. Cork lignin was found to be significantly more cross-linked than eucalyptus lignin.
doi:10.1021/bk-2000-0742.ch014
Keywords: cross-linking (PG); Eucalyptus globulus; Lignin; Quercus suber

Very high-resolution 1H MAS NMR of a natural polymeric material - Gil, A M; Lopes, M H; Pascoal Neto, C; Rocha, J (Solid State Nuclear Magnetic Resonance, 1999)
The use of ultrafast magic angle spinning (>30 kHz) in tandem with delayed echo acquisition is shown to yield very high-resolution 1H MAS NMR spectra of complex natural organic materials. For the first time, very high-resolution 1H MAS NMR spectra are reported for cork and wood components, two natural materials with great economic importance. The effect of the spinning rate on the 1H NMR spectra was evaluated with single-pulse acquisition and delayed-echo acquisition. The delayed-echo acquisition spectra presented linewidths as sharp as 67 and 25 Hz. The narrow peaks, characterised by proton spin–spin and spin–lattice relaxation, were assigned to the isotropic chemical shifts and the general spectral features were shown to correlate with the sample chemical structure. The tentative assignments of cork 1H MAS NMR signals were presented.
Keywords: 1H MAS NMR; Cellulose; Cork; Lignin; Relaxation; suberin

Phenoloxidases of the white-rot fungus Marasmius quercophilus isolated from an evergreen oak litter (Quercus ilex L.) - Tagger, S; Périssol, C; Gil, G; Vogt, G; Le petit, J (Enzyme and Microbial Technology, 1998)
A white-rot basidiomycete, Marasmius quercophilus, was isolated from an evergreen oak litter. This fungus, which very thoroughly bleaches the whole leaf area, produces laccases, a property which has not been studied before. Except on a ground leaf medium, we did not reveal phenoloxidases other than laccases. M. quercophilus is able to transform many aromatic compounds which are by-products of lignin and tannin metabolism. We observed, for example, that lignin monomers, namely p-coumaryl, coniferyl, and sinapyl alcohols are oxidized at different rates by the extracellular crude enzyme extract. The highest production of laccases is obtained with shaking cultures on malt extract supplemented with Tween 80 (0.1%) and CuSO4 (0.5 mg l 21 ). These enzymes have an optimum activity at 80°C and a stable activity at 40°C for 18 h. The extracellular crude enzyme extract medium contains three isoenzymes with pI values of 3.8, 3.5, and 3.2. It is able to significantly reduce the kappa number (21.2%) of a kraft pulp without inclusion of any mediator
Keywords: aromatic compounds; kraft pulp; laccases; Lignin; Marasmius quercophilus; phenoloxidases; tannin monomers

Decomposition of mediterranean leaf litters: A microcosm experiment investigating relationships between decomposition rates and litter quality - Cortez, J; Demard, J M; Bottner, P; Jocteur Monrozier, L (Soil Biology and Biochemistry, 1996)
he decomposition of four mediterranean species leaf litter (Sessile oak, Quercus petraea L.; Holm oak, Quercus ibex L.; Sweet chestnut, Castanea satiua Mill and beech, Fagus syluatica L.) was studied for 90 days under controlled conditions. Respiration and litter mass loss were measured in three types of microcosms: (1) Soil only; (2) Soil + l-y old litter and (3) Soil + l-y old litter + newly senescent litter (freshly fallen). Variations in chemical composition of the litters were determined before and after incubation by the pyroanalysis method. For newly senescent litters decomposition rates per day Kco, (calculated from CO, release) and K, (calculated from mass losses) fitted to the first order exponential decay decreased as follows: sessile oak (Kc,_,, = 0.0043; K, = 0.0049) > holm oak (Km, = 0.0031; K, = 0.0040) = beech (&o~ = 0.0030; K, = 0.0030) > sweet chestnut (Kc% = 0.0001; K,, = non- significant regression); For l-y old litters sweet chestnut (Ko,, = O.oo40, K, = 0.0065) > sessile oak (KEO, = 0.0035; K, = 0.0039) > beech (Kcc,, = 0.0030; K, = non-significant regression). All litters showed a reduction of lipid (mean loss 90.5%), hydrosoluble (mean loss, 54.2%), hemicellulose plus cellulose (mean loss, 40.6%) content and a relative increase of lignin content (mean gain, 34.4%). Among indicators of litter quality (C-to-N ratio, %N, %lignin, lignin-to-N ratio, HLQ), only some of them were correlated with litter decay. The best relationships were established between the decomposition rates (K,) and parameters integrating lignin contents (I = 0.997; n = 3; P < 0.01). The decomposition of l-y old litters fitted well with most of these parameters (0.999 < I < 0.997; n = 3; P < 0.01) in contrast to newly senescent litters
Keywords: Cellulose; decomposition; hemicellulose; leaf litter; Lignin; litter quality (voyant); mass loss; mineralization

13C solid-state nuclear magnetic resonance and Fourier transform infrared studies of the thermal decomposition of cork. - Pascoal Neto, C.; Rocha, J.; Gil, A.; Cordeiro, N.; Esculcas, a P.; Rocha, S.; Delgadillo, I.; de Jesus, J. D.; Correia, a J. (Solid state nuclear magnetic resonance, 1995)
The thermal decomposition of cork has been studied by Fourier transform infrared (FTIR) spectroscopy and 13C solid-state nuclear magnetic resonance (NMR) spectroscopy with cross-polarization and magic-angle spinning (CP-MAS), high-power 1H decoupling (HPDEC) and cross-polarization depolarization-polarization (CPDP). Waxes and other soluble components of cork begin to decompose at ca. 150 degrees C. This is accompanied by partial decomposition of suberin, probably initiated at the points of attachment to the cell wall. The carbohydrates begin to decompose at ca. 200 degrees C. The decomposition of lignin begins at 250-300 degrees C, while suberin undergoes further degradation. Significant amounts of coke are formed in the process. At 400 degrees C cork has been transformed into coke with traces of partially decomposed suberin. The thermal decomposition of cork is dependent on the calcination time, particularly in the 200-350 degrees C range.
The following values have no corresponding Zotero field: accession-num: 7773647
Keywords: Fourier Transform Infrared (citation); Hot Temperature; Lignin; Lignin: chemistry; Lipids; Magnetic Resonance Spectroscopy; Membrane Lipids; Membrane Lipids: chemistry; Polysaccharides; Polysaccharides: chemistry; Spectroscopy

Nitrogen immobilization in leaf litter at two Mediterranean ecosystems of SW Spain - Gallardo, Antonio; Merino, J (Biogeochemistry, 1992)
Nitrogen immobilization in relation to the dynamics of lignin and tannins in nine different types of leaf litter was investigated during a 2-yr study at two Mediterranean ecosystems of SW Spain. Net nitrogen immobilization for all the species was higher in a forest than in the more nutrient-poor soil of a shrubland. Absolute amount of lignin increased in both ecosystems in the first 2-4 months whereas tannin rapidly decreased in the same time period. Increases in lignin were significantly correlated to losses of tannins during decomposition. Initial tannin content was the best predictor of the maximum amount of immobilized nitrogen in litter in both ecosystems. Mechanisms that could explain the immobilization of nitrogen in litter are discussed.
Keywords: immobilization; leaf litter decomposition; Lignin; Mediterranean ecosystem; nitrogen; tannin

Determination of hemicellulose, cellulose and lignin contents of dietary fibre and crude fibre of several seed hulls. Data Comparison - Saura-Calixto, F; Cañellas, J; Garcia-Raso, J (Z Lebensm Unters Forsch, 1983)
The contents of hemicellulose, cellulose and lignin in neutral-detergent fibre, and acid-detergent fibre in hulls of hazelnuts, peanuts, coconuts, sun- flower seeds, p u m p k i n seeds, acorns and chestnuts were determined. Similar cell-wall characteristics for sunflower-acorn, peanut-pumpkin and hazelnut-chest- nut pairs can be deduced from their similar composi- tion. High amounts of hemicellulose and lower ones of cellulose and lignin are dissolved in the process of de- termining crude fibre. The results are discussed.
Keywords: Cellulose; hemicellulose; hulls (PG); Lignin

The resistance of cork to decay by wood-destroying molds - DeBaun, Robert M; Nord, F F (Archives of Biochemistry and Biophysics, 1951)
A new method for the determination of the lignin in cork has been reported. This procedure gives values ca. 25–30%. It is based on the colorimetric estimation of the lignin released by autoclaving with alkali. Using this method it was shown that cork is highly resistant to decay by brown-rot wood-destroying molds. This is attributed to the protective action of the suberin or to the presence in the cork of substances toxic to the molds.
APS
Keywords: Cork; Lignin; molds; resistance